2016
DOI: 10.1108/cdi-04-2015-0063
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical plateau and turnover intention of employees at the career establishment stage

Abstract: Purpose Applying the theory of work adjustment (TWA), the purpose of this paper is to investigate whether the effect of hierarchical plateau on the turnover intention of employees at the career establishment stage is mediated by job satisfaction and moderated by person-job fit. Design/methodology/approach A survey method was used and data were collected from 248 Chinese employees at the career establishment stage. Hierarchical regression analysis and moderated mediation analysis were used to test the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 57 publications
4
20
0
1
Order By: Relevance
“…When employees find their jobs challenging, they are likely to exhibit high performance (Kristof-Brown et al, 2005), seen as promotable (Hoobler, Wayne, & Lemmon, 2009), and consequently experience less hierarchical plateau. Indeed, in a recent study, Xie, Xin, and Bai (2016) reported an association between person–job fit and hierarchical plateau, but in this study, person–job fit was measured with a single item. Hypothesis 3: Demands-ability fit will mediate the relationship between career adaptability and (a) job content plateau and (b) hierarchical plateau. …”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 81%
See 2 more Smart Citations
“…When employees find their jobs challenging, they are likely to exhibit high performance (Kristof-Brown et al, 2005), seen as promotable (Hoobler, Wayne, & Lemmon, 2009), and consequently experience less hierarchical plateau. Indeed, in a recent study, Xie, Xin, and Bai (2016) reported an association between person–job fit and hierarchical plateau, but in this study, person–job fit was measured with a single item. Hypothesis 3: Demands-ability fit will mediate the relationship between career adaptability and (a) job content plateau and (b) hierarchical plateau. …”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 81%
“…The job becomes routine, boring, and unchallenging (Allen et al, 1999). In general, previous research has reported that plateaus are negatively related to job satisfaction (e.g., Chao, 1990; Jung & Tak, 2008), organizational commitment (Jung & Tak, 2008; McCleese & Eby, 2006), task performance (Stout, Slocum, & Cron, 1988), and citizenship behaviors (Hurst et al, 2017) and positively related to absenteeism (Near, 1985), turnover intentions (Xie et al, 2015; Xie, Xin, & Bai, 2016), and turnover (e.g., Veiga, 1981).…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Such claims stem from the evidence that satisfaction is highly predictive of job performance and other attitudinal variables such as turnover intentions(Judge, Thoresen, Bono, & Patton, 2001;Tett & Meyer, 1993). For example,Armstrong-Stassen and Ursel (2009) andXie et al (2016) both found that satisfaction was a mediator of the effects of job content, but not hierarchical plateau, on intention to remain in the organisation. More recently,Hurst et al (2017) demonstrated that job satisfaction mediated the relationship between job content plateau and organisational citizenship behaviour (as a form of job performance) among hospital workers.…”
mentioning
confidence: 99%
“…Edwards [52] defined person-job fit as the match between personal skills and vocational requirements, or as the match between personal requirements and vocational characteristics. Person-job fit indicates the correspondence between job reinforcement system and need system of the individual [53]. Hence, person-job fit is an important concept both for employees and recruiters.…”
Section: Theory and Hypothesesmentioning
confidence: 99%